2003
DOI: 10.1146/annurev.physiol.65.092101.142243
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hypertrophy: The Good, the Bad, and the Ugly

Abstract: Cardiac hypertrophy is the heart's response to a variety of extrinsic and intrinsic stimuli that impose increased biomechanical stress. While hypertrophy can eventually normalize wall tension, it is associated with an unfavorable outcome and threatens affected patients with sudden death or progression to overt heart failure. Accumulating evidence from studies in human patients and animal models suggests that in most instances hypertrophy is not a compensatory response to the change in mechanical load, but rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
1,068
0
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,309 publications
(1,097 citation statements)
references
References 224 publications
10
1,068
0
19
Order By: Relevance
“…In the long‐term, however, the initial response may become maladaptive, which is characterized by progressive LV dilation with an inadequate cardiac pumping activity 38, 39. We found in this study that instead of cardiac hypertrophy, decreased LVEF was observed in mice at 4 weeks after TAC, and exogenous HMGB1 overexpression further aggravated the impairment of cardiac function from this perspective.…”
Section: Discussionmentioning
confidence: 54%
“…In the long‐term, however, the initial response may become maladaptive, which is characterized by progressive LV dilation with an inadequate cardiac pumping activity 38, 39. We found in this study that instead of cardiac hypertrophy, decreased LVEF was observed in mice at 4 weeks after TAC, and exogenous HMGB1 overexpression further aggravated the impairment of cardiac function from this perspective.…”
Section: Discussionmentioning
confidence: 54%
“…3 In an attempt to maintain the necessary blood pressure for organ perfusion, chronic activation of autonomous regulatory mechanisms initiate a vicious cycle of maladaptive structural and functional events that progressively affects all parts of the cardiovascular system. 4,5 Commonly used drugs combating this process tend to attenuate the neurohormonal overactivation, however, by virtue of their mechanism, act enforcedly symptombased, and slow down disease progression only. 6,7 However, steady improvement of our understanding of cellular and molecular processes that contribute to HF pathogenesis prompts continuous development of innovative experimental therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the initial stimulus, the heart counters these insults with a mechanism known as hypertrophy -a compensatory enlargement of the heart -due to increased biomechanical stress (6).…”
mentioning
confidence: 99%